(untitled) (ANGON: Journal of Animal Science and Technology, 2020)
Background. This study is entitled "DOD Abnormalities and Salable Duckling in Duck Eggs Smeared with Vinegar at the End of Hatching". This research was conducted from 3 May 2018 to 1 June 2019 at the Poultry Production Laboratory, Faculty of Animal Husbandry, Jenderal Soedirman University, Purwokerto. This study aims to examine the effect of egg smearing using vinegar acid liquid with different concentrations in the hatching process against DOD Abnormalities and Salable Duckling in Tegal duck eggs. Materials and Methods. The material used in this research is Tegal duck eggs that are worth hatching as many as 200 eggs. The experiments were carried out using the experimental method and using a completely randomized design (CRD). The dyeing treatment consisted of P0 = 0% vinegar acid, P1 = 10% vinegar acid, P2 = 20% vinegar acid, each for 40 eggs. Each treatment was repeated 4 times. The ingredients used are acetic acid or vinegar and aquadest acid. The tools used were a set of 4 incubators, 100 ml measuring cups 1 unit, 10 ml measuring pipettes, 1 unit filler and 2 brushes. Results. The results of the analysis of variance showed that the application of vinegar to the duck eggs at the end of hatching had a very significant effect (P <0.01) on DOD Abnormalities and Salable Duckling. Conclusion. Based on these studies it can be concluded that dipping Tegal duck eggs in 10% vinegar acid concentration at the end of hatching decreases DOD abnormality and increases Salable Duckling.